THE FACTORS AFFECTING IMPULSE BUYING (DESCRIPTION STUDY ON INDOMARET AND ALFAMART CONSUMERS, PANORAMA LAKE ROAD, BENGKULU CITY) - Donny Christopel; Sulisti Afriani; Tito Irwanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
Retail growth business in Bengkulu city is getting attracted. Especially minimarket. The growth of retail business cannot separate from society need who need practice, comfortable and time saving. Retail must be active and always innovate in productivity or service, so they can compete in market place. Consumer who feel comfort with store environment also supported by emotional motivation which can increase impulse buying. The purpose of this research is to find out the factors which influence impulse buying on consumer of Indomaret and Alfamart at Danau Street Panorama Bengkulu. This research was conducted by using questionnaire as the research tool. The samples were taken by using non-probability method with accidental technique, the research was conducted a week on 74 consumers, 37 consumers for each store. Analysis were conducted by using rating scale, it is a raw data which obtained then being read in qualitative understanding. The result of this research shows that dominant factors influencing impulse buying on consumers of Indomaret and Alfamart is Elaborate Package displays factor the score 655 for Indomaret and 660 for Alfamart, the second factor is Product samples with the score 645 for Indomaret and 631 for Alfamart, the third factor is store promotional material for consumer with a score of 608 for Indomaret and Place based for media for Alfamart score is 627. The last factor or the lowest which influence Impulse Buying for consumer is Place base media factor for Indomaret with the score of 603 and Store promotional material factor for Alfamart with the score of 614.